STRATEGI BERTAHAN HIDUP KELUARGA PETANI KELAPA SAWIT DI DURI, KABUPATEN BENGKALIS - Lumban raja, Febrini Estomihi; Daud, Daud (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2024)
This research aims to describe the social and economic life of oil palm farmers in Pematang Obo Village, the problems faced by oil palm farmers in Pematang Obo Village and survival strategies for oil palm farmers in Pematang Obo Village. The research method used is qualitative with a descriptive approach. Data collection techniques are observation, interviews and documentation. The results of this research show that the social life of oil palm farmers is the formation of patron-client relationships between farmers and tauke, while the economic life of farmers is determined by the income they generate from the oil palm harvest, the amount of harvest depends on the quality of the oil palm fruit. The problems faced by farmers in Pematang Obo Village are unstable palm oil prices, high fertilizer prices, flooding (high rainfall), failed seeds, irregular maintenance, cases of palm oil theft, different selling prices, access to Plantation. The strategy implemented by farmers in Pematang Obo Village consists of 3 strategies, namely active strategy, passive strategy, network strategy. Active strategies include opening side businesses such as opening a food stall, opening a sewing business, and opening a vegetable cultivation business. Passive strategies in the form of saving and prioritizing important things first, and networking strategies in the form of lending money to tauke and banks, participating in social gatherings (jula-jula) and getting into debt